If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3m + -2) = 20m Reorder the terms: 6(-2 + 3m) = 20m (-2 * 6 + 3m * 6) = 20m (-12 + 18m) = 20m Solving -12 + 18m = 20m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-20m' to each side of the equation. -12 + 18m + -20m = 20m + -20m Combine like terms: 18m + -20m = -2m -12 + -2m = 20m + -20m Combine like terms: 20m + -20m = 0 -12 + -2m = 0 Add '12' to each side of the equation. -12 + 12 + -2m = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -2m = 0 + 12 -2m = 0 + 12 Combine like terms: 0 + 12 = 12 -2m = 12 Divide each side by '-2'. m = -6 Simplifying m = -6
| 12-(x+4)=-2(x-1)-2 | | -95=n-30 | | 2(5y+13)-5.7=203 | | X/14=85 | | (2x-3/4)-(2x-1/3)=1 | | 8w-26=-6(w+9) | | 4+p=56 | | -t+6=-t+9 | | 6(v+7)=-7v-36 | | 2.6+3x=97.4 | | 6t+7+3t=5t+27 | | -3b-7=20 | | 7y-5-2y=-20 | | 20=4v+16 | | 5x-16=4x-6 | | 3(x+5)-10x+7=50 | | 5v+v-120=0 | | (4x-16)/(3-x)*(x-3)/4 | | a/a | | -4r^2=-152 | | 80-4(3x+10)=-12x+120 | | 5x^2+3=68 | | 3g-2=5g | | 3(p-1)=3p-2 | | -x+7=2x+13 | | -7w-35=2(w+5) | | X/6=54 | | -x+5=2x-11 | | 5x-12=-2y+3 | | -3/4x-7/8 | | 8(v+7)=-5v-48 | | 3(13-2a)=-13+a |